Multi-sectoral policy platform to promote best pratices and pilot programs around biodiversity in Kenya - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
The multi-stakeholder policy platform enabled the endorsement of the first ever biodiversity conservation policy for Kenya's 47 counties, which is ready for uptake. The approach has raised interest from neighbouring countries.